Institutional tools for managing the development of the export potential of textile industry enterprises - Durru, D.K.; Yessirkepova, A.M.; Aliyeva, Zh.T.; Yessengeldina , A.S. (BUKETOV BUSINESS REVIEW, 2023)
Object: The article presents directions for the effective use of institutional tools to increase the export potential of domestic textile products. Methods: The article used statistical data on export trade in textile products as an information basis. In the course of the study, systematic and statistical methods were used. The authors of the article studied the works of scientists regarding the means of stimulating the export of textile products: state guarantees for the export of industrial products, indicators for assessing the effectiveness of exports, competition problems, provision of modern equipment, pricing policy, skilled labor, the possibility of digital transformation. Findings: The authors analyzed data on the export opportunities of foreign countries and Kazakhstan to develop a strategy for promoting textile products to international markets. The authors of the article identified problems that impede the development of exports of textile products: technical and technological backwardness; insufficient production capacity; low labor productivity due to a shortage of specialists; lack of means of production and associated accessories; non-competitiveness of finished products due to high cost. Conclusions: The article identified the existing institutional tools for the development of the export potential of textile enterprises for the future: development of an export acceleration program that is not directly related to foreign trade financing; introduction of a comprehensive ecosystem of textile enterprises based on the use of Big Data Processing and artificial intelligence technologies; provision of insurance protection for exporters of textile products abroad; technological modernization of an export acceleration program that is not directly related to foreign trade financing.